Human epidermal keratinocytes death and expression of protein markers of apoptosis after ionizing radiation exposure - Sharon Wong (International Journal of Cancer Therapy and Oncology, 2013)
Purpose: Knowledge of the pathophysiology of the irradiated skin is important to understand the tolerance and cosmetic response of the human skin to radiation. There are limited studies on the effect of radiotherapy dosage and fraction size in inducing apoptotic cell death in human skin. The expression of apoptotic biomarkers within a controlled population in different fractionation schemes has also never been studied. This study aims to investigate radiation induced apoptotic cell death in human skin cells after fractionated radiation exposure and the expression of unique biomarkers that reflect cell death or biology using multiplexed immunoassays. Methods: Breast skin biopsies were obtained from a single individual and divided into small pieces. Each piece was irradiated under different radiotherapy treatment fractionation schedules to a total dose of 50Gy. The irradiated skin tissues were analysed using Tunnel, immunohistochemistry and Western blot assays for expression of apoptotic keratinocytes and biomarkers (p53, p21, and PCNA). Haematoxylin and eosin (H&E) immunostaining was performed to study the morphological changes in the skin cells. Results: Radiation is mostly absorbed by the epidermal layers and observed to damage the epidermal keratinocytes leading to the activation of apoptotic proteins. Apoptotic proteins (p53, p21 and PCNA) were confirmed to be up-regulated in radiation exposed skin cells as compared to normal skin cells with no radiation. There is strong correlation of apoptotic protein expressions with increased radiation dosage and dose fractionation. Statistical analysis with ANOVA revealed a significant increase of PCNA and p21 expression with increased radiation dosage and dose fractionation (p < 0.05). Immunohistochemically, 14 % (range 10.71% to 17.29%) of the keratinocytes were positive for PCNA and 22.5% (range 18.28% to 27.2%) for p21 after 2Gy of irradiation.  The most widespread, intense and uniform staining for PCNA and p21 was observed in skin that had received 50Gy of irradiation. The maximum expression of p53 (range 37.09% to 50.91%) was reached at 10Gy. Conclusion: Findings from this study will assist clinicians in predicting radiation induced skin toxicity with the current changes in radiation fractionation protocols. ----------------------------------- Cite this article as: Wong S, Chor HH, Moothy S, Ong CT, Phan TT, Lu JJ. Human epidermal keratinocytes death and expression of protein markers of apoptosis after ionizing radiation exposure. Int J Cancer Ther Oncol 2013; 1(2):01027. DOI: http://dx.doi.org/10.14319/ijcto.0102.7